Performance of Ni/dolomite pellet catalyst on gas distribution from cassava rhizome gasification with a modular fixed-bed gasifier. Issue 9 (3rd May 2017) - Sricharoenchaikul, V.; Atong, D.; Sornkade, P.; Nisamaneenate, J.
ABSTRACT: Thermal conversion of cassava rhizome was performed using a modular downdraft gasifier with the addition of Ni-based catalysts as promising tar eliminating and produced gas upgrading techniques. The activities of a synthesized 5% Ni/dolomite pellet catalyst prepared by impregnation method were investigated in a secondary reactor downstream of the gasifier. High reforming activity of the Ni/dolomite pellet catalyst on tar reduction was achieved. The conversion to H2 and CO was improved via steam reforming of methane and char reaction with CO2 . Moreover, the formation of CH4 and C x H y was diminished through the tar or condensable hydrocarbon reformed on the catalyst surface. The carbon and hydrogen conversions of cassava rhizome with prepared catalyst were 83.79% and 61.78%, respectively, at an air flow rate of 1.98 m 3 /hr. At this condition, tar formation was low, while the lower heating value was 4.39 MJ/m 3 and H2 to CO molar ratio was 1.22. Generally, the addition of a catalyst not only enhanced gas production, but also reduced tar and particulate matter generation; thus, its implementation should help lessen the pollution control requirement and cost of operation, while allowing higher quality fuel gas production.